Development and Evaluation of Vaginal gel Containing Anti-Fungal Agent in Combination with Probiotic Bacteria Without API - Priti Balasaheb Shinde,; Ankit Singh,; Amit Kasabe, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Probiotic Lactobacillus strains have garnered significant interest due to their potential health benefits, including improving gut health and immune function. This study investigates the characteristics and growth of four subcultured Lactobacillus strains—Lactobacillus plantarum, Lactobacillus casei, Lactobacillus acidophilus, and Lactobacillus rhamnosus (LGG)—in various conditions. Growth patterns were monitored in MRS broth, and morphological, microscopic, and colony characteristics were recorded. The study further explores the viability of Lactobacillus strains under acidic pH and bile salt conditions, assessing the impact of these factors on their growth and survival. Results show that while Lactobacillus strains demonstrated considerable resilience in acidic environments (pH 1 and pH 3), their growth was notably affected by higher bile concentrations. L. rhamnosus exhibited the highest tolerance to bile salts, whereas L. plantarum showed the greatest resilience at low pH. The viable cell counts across all strains varied significantly under different conditions, providing valuable insight into the probiotic potential of these strains for applications in functional foods and supplements. The findings suggest that specific Lactobacillus strains possess unique traits, offering avenues for their use in formulations designed to survive harsh gastrointestinal conditions.